Prosesi Adat (Merariq) dalam Kacamata Hukum Pidana di Masyarakat Lombok Tengah (Studi Kasus di Kelurahan Gerantung Praya Tengah Kabupaten Lombok Tengah NTB) - Azhari, Doni (Al-Jinayah : Jurnal Hukum Pidana Islam, 2023)
This article discusses the criminal aspects in the procession of traditional ceremonies (merariq) of the Central Lombok community (Case Study in Gerantung Village, Central Praya, Central Lombok, NTB). The main challenge of this research is to identify the criminal elements in the procession of merariq customs of the Central Lombok community. For this reason, using an empirical study approach, this researcher collected data through interviews with traditional leaders, community leaders, and authorities. This study concludes that the custom of merariq for the people of Gerantung Village does not conflict with existing customs, even in practice the community will commit criminal acts if they violate customs and state regulations, one of which is Articles 330 and 332 of the merariq custom which have rules that are in line with the practice and enforcement of law in the Merariq tradition.